Representations of the real forms of calibrated analogue of the Lie algebra - Ostrovsky, V.L.; Silvestrov, S.D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Real-valued forms of the Z_2^n -graded analogue of the Lie algebra sl(2, C) are described and their irreducible representations are studied.